Curcuma amarissima Extract Activates Growth and Survival Signal Transduction Networks to Stimulate Proliferation of Human Keratinocyte - Wutigri Nimlamool; Saranyapin Potikanond; Jirapak Ruttanapattanakul; Nitwara Wikan; Siriporn Okonogi; Salinee Jantrapirom; Pornsiri Pitchakarn; Jirarat Karinchai (Biology, 2021)
Many medicinal plants have been used to treat wounds. Here, we revealed the potential wound healing effects of Curcuma amarissima (CA). Our cell viability assay showed that CA extract increased the viability of HaCaT cells that were cultured in the absence of serum. This increase in cell viability was proved to be associated with the pharmacological activities of CA extract in inducing cell proliferation. To further define possible molecular mechanisms of action, we performed Western blot analysis and immunofluorescence study, and our data demonstrated that CA extract rapidly induced ERK1/2 and Akt activation. Consistently, CA extract accelerated cell migration, resulting in rapid healing of wounded human keratinocyte monolayer. Specifically, the CA-induced increase of cell monolayer wound healing was blocked by the MEK inhibitor (U0126) or the PI3K inhibitor (LY294002). Moreover, CA extract induced the expression of Mcl-1, which is an anti-apoptotic protein, supporting that CA extract enhances human keratinocyte survival. Taken together, our study provided convincing evidence that Curcuma amarissima can promote proliferation and survival of human keratinocyte through stimulating the MAPK and PI3K/Akt signaling cascades. These promising data emphasize the possibility to develop this plant as a wound healing agent for the potential application in regenerative medicine.